Three profiles of Australian climate change activism have both unique and overlapping motivators and barriers - Kathleen C. Whitson; Peta Callaghan; David Thorpe; Anastasia Ejova (Communications Earth & Environment)
Abstract Since non-violent activism is known to be effective in achieving policy change, organisations seeking to encourage climate activism would benefit from an evidence base describing activism behaviours, motivators, and barriers among people higher, lower, and in between in terms of climate activism involvement. We surveyed 519 Australians alarmed by climate change regarding participation in 18 activism behaviours. A latent class analysis identified three activism levels: Least (23%), Moderate (55%), and Most (22%). The Most Active participants were at least 75% likely to engage in 13 behaviours. The only demographic difference between classes is that participants in the Least Active class were younger. Across classes, the most common reported motivators related to issue importance and action efficacy. Reported barriers were more behaviour-specific, with frequent references to lack of experience and knowledge for financial activism and engagement with climate organisations. Six practical applications for promoting climate activism are discussed.